The ventilatory component of the muscle metaboreflex is overstimulated in transthyretin cardiac amyloidosis patients with poor aerobic capacity - Monfort, Astrid; Thevenet, Eugenie; Enette, Lievyn; Fagour, Cedric; Inamo, Jocelyn; Neviere, Remi (Frontiers in Physiology, 2023)
Background: The exercise pressor reflex, i.e., metabo- and mechano- reflex, partially regulates the control of ventilation and cardiovascular function during exercise. Abnormal exercise pressor reflex response has been associated with exaggerated ventilatory drive, sympatho-vagal imbalance and exercise limitation in chronic heart failure patients. Whether metaboreflex is over-activated and participate to poor aerobic capacity in patients with transthyretin cardiac amyloidosis (CA-TTR) is unknown. Methods: We aimed to determine whether metaboreflex is over activated in CA-TTR patients, as well as to assess its relationships with autonomic imbalance and impaired aerobic capacity. Twenty-three CA-TTR patients underwent a thorough evaluation including cardiac biomarkers, echocardiography, cardiopulmonary exercise testing, electrochemical skin conductance and muscle metaboreflex assessment. Results: Control subjects and CA-TTR patients had similar metaboreflex sensitivity for cardiac index (4.96±5.63% vs. 1.63±13.31%) and mean systemic arterial pressure (0.16±3.04% vs. 3.56±18.54%). Metaboreflex sensitivity for systemic vascular resistance (-18.64±6.91 vs. 3.14±32.52%) and minute-ventilation (-9.65±14.83 vs. 11.61±32.19) responses was markedly higher in CA-TTR patients respectively). Metaboreflex sensitivity for mean arterial pressure and mean systemic vascular resistance responses displayed inverse correlations with electrochemical skin conductance (fESC) values (r=-0.446, P=0.033 and r=-0.552, P=0.006, respectively). Metaboreflex sensitivity analyzed in term of ventilation response displayed inverse correlation with peak VO2 in percent of predicted absolute values (r=-0.613, P=0.034). Conclusion: The major novel finding appears to be an excessive ventilatory response to metaboreflex activation in CA-TTR patients. This abnormal ventilatory component of the muscle metaboreflex was associated with poor aerobic capacity, which may be involved in exercise intolerance in CA-TTR patients.